Black Americans and Organized Labor : A New History - Moreno, Paul D., 1965- (Book collections on Project MUSE., 2006)
In Black Americans and Organized Labor, Paul D. Moreno offers a bold reinterpretation of the role of race and racial discrimination in the American labor movement. Moreno applies insights of the law-and-economics movement to formulate a powerfully compelling labor-race theorem of elegant simplicity: White unionists found that race was a convenient basis on which to do what unions do-control the labor supply. Not racism pure and simple but ""the economics of discrimination"" explains historic black absence and under-representation in unions. Moreno's sweeping reexamination stretches from the an